Knowledge, Attitude and Uptake of Pap Smear among Female Healthcare Professionals in a Nigerian Teaching Hospital - Olarinoye AO; Shiru MM; Ubom AE; Olabinjo AO; Abdul IF; Ijarotimi OA; Nyeche S; Oriji PC; Amadi L; Ikimalo JI (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: Despite the high prevalence of cervical cancer (CC) in Nigeria, the uptake of screening services, including Pap smear, remains poor, even amongst healthcare providers. Objective: To assess Pap smear knowledge, attitude, and uptake among female healthcare professionals (FHPs). Methods: A cross-sectional descriptive study was conducted at the University of Ilorin Teaching Hospital (UITH), Kwara State, Nigeria, using a self-administered questionnaire. Results: A majority (343, 98.6%) of the FHPs knew Pap smear. Five (26.3%) medical laboratory scientists did not know what a Pap smear was. All the nurses, doctors, pharmacists, physiotherapists and medical social workers knew Pap smear. Only a fifth (71; 20.4%) of the FHPs had ever done a Pap smear. The most common reason cited for not having done a Pap smear was lack of time (109; 31.3%). There was a relationship between age and uptake of Pap smear (p = 0.024). Only 188 (54%) of the FHPs had ever recommended Pap smear to other women. Conclusion: Despite the high level of knowledge of Pap smear amongst FHPs in Nigeria, attitude and uptake remain poor. There is a need for further training and education of FHPs on the benefits of CC screening to increase their uptake and improve their effectiveness in promoting positive attitudes towards CC screening and prevention in the general population.